Stapled Transanal Resection of Rectum (STARR) Procedure for Obstructed Defecation Syndrome Caused by Rectocele and Rectal Intussusception: An Initial Experience (Journal of Rangpur Medical College, 2024)
Background: Obstructed defecation syndrome (ODS) is a troublesome condition for the patient which affect the quality of life. It is difficult to determine the single effective modality of treatment of ODS. Though ODS is more common in the women than men, rate of diagnosis of ODS in female is lower due to shyness of patient to visit to doctor. Objective: Study was conducted to see the effectiveness of stapled transanal resection of rectum (STARR) procedure for obstructed defecation syndrome caused by internal rectal prolapse and anorectocele. Methods: This prospective study was done including 37 patients (female 35 and male 02). These patients had undergone STARR procedure from January 2015 to September 2023 in Rangpur medical college and two private hospitals. Only those patients had undergone STARR procedure who suffered from ODS due to internal rectal prolapse or rectocele and failed to response to adequate first line medical therapeutics. Patients were diagnosed by careful evaluation of history, Longo's ODS score, DRE, proctoscopy, colonoscopy, cinedefecography and MR defecography. Patients were followed up at 1, 3 and6 months after surgery. During follow up patientssatisfaction was evaluated by comparing preoperative and postoperative score. Results: Average time needed for each procedure was 45±10 minutes and average hospital stay was 4 days. No patient needed readmission for any complication, but 3 patients came back for minor bleeding, 3 patients for increasing frequency of defecation and 1 patient for persistent anal pain where no definite cause was detected. At 6 months follow up significant improvement in Longo's ODS score, constipation score and quality of life was observed. Mean Longo’s ODS score was 15.75±1.98 and 7.05±5.70 at preoperative and six months post operative folowup respectively (p=